2018
DOI: 10.1002/pds.4417
|View full text |Cite
|
Sign up to set email alerts
|

Polydrug epidemiology: Benzodiazepine prescribing and the drug overdose epidemic in the United States

Abstract: These findings shed light on the polydrug epidemiology of the overdose epidemic. Overdose deaths are highest where elevated opioid and benzodiazepine claims coexist. Overdose levels may reflect polydrug use and misuse, requiring clinical and policy responses beyond reducing opioid prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Five studies reported nine multivariable models of factors associated with opioid-related mortality or opioid-related factors associated with nonopioid-related deaths in older adults (Table 14). 90,107,[113][114][115] The models analyzed all-cause death; opioid-related death; nonopioid-specific death, including COPD-or pneumonia-related death; and drug overdose death (any drug). The models evaluated factors related to demographics; opioid use, misuse, and prescription; socioeconomic and related factors; clinician factors; and other substance use.…”
Section: Evidence Basementioning
confidence: 99%
“…Five studies reported nine multivariable models of factors associated with opioid-related mortality or opioid-related factors associated with nonopioid-related deaths in older adults (Table 14). 90,107,[113][114][115] The models analyzed all-cause death; opioid-related death; nonopioid-specific death, including COPD-or pneumonia-related death; and drug overdose death (any drug). The models evaluated factors related to demographics; opioid use, misuse, and prescription; socioeconomic and related factors; clinician factors; and other substance use.…”
Section: Evidence Basementioning
confidence: 99%
“…The most frequent poisoning in adults over the age of 20 came from analgesics (11.2%). This was followed by hypnotics, sedatives and antipsychotics (9.8%) and antidepressants (7.2%), which have high potential to depress the central nervous system and form pharmacological interaction with other drugs, foods and alcohol 5 . Misusing medications like this can induce liver, kidney and central nervous system damage, which are a physical and emotional burden on the population and have a negative impact on health system finances 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Opioids accounted for 61% of all drug-related overdoses in 2014 (1). Overdose death rates are highest when opioids and benzodiazepines are combined (2). It has become increasingly clear that over-prescription of these medications in the past two decades is a primary upstream driver of the crisis.…”
Section: Introductionmentioning
confidence: 99%